Characteristics of Patient Complaints in a Large Tertiary Hospital in China: A Longitudinal Analysis from 2022 to 2024 - Baoxiang Wang; Xuyuan Kuang (Healthcare, 2026)
Background: Patient complaints provide critical insights into healthcare quality and patient experience, serving as a direct feedback mechanism for service improvement. Objective: This study aimed to characterize major complaint categories, departmental distribution, personnel attribution, and resolution effectiveness of patient complaints at a large Chinese tertiary hospital using empirical data from 2022 to 2024. Methods: A retrospective observational design was conducted on complaint records (2022: n = 187; 2023: n = 192; 2024: n = 201) at Xiangya Hospital. All data presented are empirically observed records from the hospital’s internal complaint management system; no hypothetical projections or modelled data are included. Complaints were independently categorized into six themes by two researchers (Cohen’s κ = 0.84). Resolution effectiveness was coded by the hospital’s complaints office. Descriptive statistics and chi-square tests were performed using R software. A complementary SWOT analysis was conducted to assess institutional complaint management capacity. Results: Service attitude (25.1% in 2022, 23.4% in 2023, 21.9% in 2024) and communication (20.3%, 18.8%, 17.2%) constituted the largest complaint categories, both showing significant declining trends (χ2_trend = 6.54, df = 2, p = 0.038 for communication; χ2_trend = 5.98, df = 2, p = 0.045 for service attitude). The top three departments with the highest complaint volumes were General Surgery (16.6% in 2022), Gastroenterology (12.8%), and Otolaryngology (9.6%). Seasonal analysis revealed that the third quarter (July–September) was the peak complaint period (29.4% in 2022). The overall effective resolution rate improved from 62.3% in 2022 to 67.7% in 2023 and 71.5% in 2024 (χ2_trend = 8.12, df = 2, p = 0.017). Treatment outcome complaints showed a relative increase from 18.2% in 2022 to 20.1% in 2024, while billing/administrative complaints increased from 15.0% to 17.4%. Conclusion: Systematic analysis of patient complaints effectively identifies recurrent issues and informs quality improvement strategies. A balanced focus on both “soft skills” (e.g., communication, empathy) and “hard system” factors (e.g., processes, resources) is essential. Continuous monitoring and responsive feedback mechanisms are crucial for sustaining improvements in patient safety and satisfaction.